Pharmacological prevention of postictal agitation after electroconvulsive therapy—A systematic review and meta-analysis - Feenstra, Thomas C.; Blake, Yvonne; Hoogendoorn, Adriaan W.; Koekenbier, Krista; Beekman, Aartjan T. F.; Rhebergen, Didi (Frontiers in Psychiatry, 2023)
Background: Postictal agitation (PIA) after electroconvulsive therapy (ECT) is an important clinical problem estimated to occur in 7-36% of patients and recur in 19-54%. PIA has the potential to cause dangerous situations for the patient and staff members aside from the financial impact. To date, it is unclear which pharmacological interventions should be used in the management of PIA. This study aims to systematically review the (preventative) pharmacological treatment options for PIA after ECT. Method: A systematic search was done in PubMed, EMBASE, PsycINFO and Web of Science from inception till 10-11-2022. We included randomized trials with any pharmacological intervention or comparison and a predefined outcome measure on PIA. Studies that solely included patients with neurodegenerative disorders or stroke were excluded. Data quality was assessed with the RoB2 and GRADE. Meta-analysis was performed if possible. This study was registered on PROSPERO under CRD42021262323. Results: We screened 2204 articles and included 14 studies. Dexmedetomidine was investigated in 10 studies. Alfentanil, lignocaine, esmolol, midazolam, propofol, ketamine, haloperidol and diazepam were each studied in only one study. Meta-analysis revealed an OR of 0.45 (0.32-0.63), a moderate effect size, in favor of dexmedetomidine compared to placebo to prevent PIA with very low heterogeneity (I2 = 0%). The certainty of evidence was moderate. The other interventions studied were all found to have a low certainty of evidence. Conclusions: For clinical practice, we believe that our results indicate that dexmedetomidine should be considered for prevention of PIA in patients that have previously experienced PIA.